The Spread of the Soil-Borne Pathogen Fusarium solani in Stored Potato Can Be Controlled by Terrestrial Woodlice (Isopoda: Oniscidea) - Anett Mészárosné Póss; Anikó Südiné Fehér; Franciska Tóthné Bogdányi; Ferenc Tóth (Agriculture, 2021)
Fusarium solani, a soil-borne pathogen of stored potato may be disseminated, and thus, the damage caused by the pathogen may be aggravated by the grazing activities of arthropods. To investigate whether terrestrial woodlice contribute to the spread or, instead, to the control of F. solani, we launched a series of pilot experiments. First, a laboratory feeding trial was set up to find whether and to what extent woodlice consume the mycelia of fungal pathogens, namely, Aspergillus niger, F. solani, Macrophomina phaseolina, and Sclerotinia sclerotiorum. This was followed by a second set of experiments to simulate storage conditions where potato tubers, either healthy or infected with F. solani, were offered to woodlice. We found that: (1) F. solani was accepted by woodlice but was not their most preferred food source; (2) the presence of woodlice reduced the spread of F. solani among potato tubers. Our results suggest that the classification of terrestrial woodlice as “storage pests” needs re-evaluation, as isopods have the potential to disinoculate infective plant remnants and, thus, reduce the spread of storage pathogens.